ANALISIS KONDISI KEUANGAN MENGGUNAKAN METODE ZAVGREN PADA CV GREN TROPICAL PERIODE 2015-2017 - suhendi, amalia faradilah; Samsudin, Acep; Mulia, Faizal (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
This study aims to determine how the company's financial condition on CV. Green Tropical during the period 2015-2017 using the Zavgren method. Company data is obtained from the company's financial statements. The data analysis technique used is the Zavgren method. The results of this study are that in 2016 the value (Pi) is relatively high and tends to increase. Increasing the value (Pi) is influenced by the increase in the TURN variable which has a constant +0.11 and in 2017 the value (Pi) returns to decrease. The decrease in value (Pi) is influenced by a decrease in the CASH variable which has a constant -10.78 and a decrease in the TURN variable which has a constant +0.11. the improvement in the company's financial condition improved due to the positive amount of working capital + fixed assets of the company and was triggered by the increasing number of sales which caused a decrease in the TURN ratio. The company's financial condition calculated using the Zavgren method shows that the overall financial condition of the company during the 2015-2017 period is included in the fluctuating critical category which means it can be said that the company's financial condition shows that the company's financial condition for the period 2015-2017 is stable.